2023
DOI: 10.1021/acscatal.3c01962
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Insights into Bienzymatic Cascade for Mediatorless Bioelectrochemical Ethanol Oxidation with Alcohol and Aldehyde Dehydrogenases

Abstract: The efficient utilization of biomass fuels is a critical component of a sustainable energy economy. Via respiration, acetic acid bacteria can oxidize biomass ethanol into acetic acid using membrane-bound alcohol and aldehyde dehydrogenases (ADH and AlDH, respectively). Focusing on the ability of these enzymes to interact directly and electrically with electrode materials, we constructed a mediatorless bioanode for ethanol oxidation based on a direct electron transfer (DET)-type bienzymatic cascade by ADH and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 102 publications
2
3
0
Order By: Relevance
“…UQ 10 was quantified as 1% of the molar amount of rFDH, indicating that UQ 10 bound weakly and partially to the enzymes. This is consistent with the relatively low resolution of the densities, and similar results have been confirmed in the case of ADH and AlDH from G. oxydans . Furthermore, we confirmed a clear cavity around the FAD catalytic site in the top view of the structure (Figure C).…”
Section: Resultssupporting
confidence: 90%
“…UQ 10 was quantified as 1% of the molar amount of rFDH, indicating that UQ 10 bound weakly and partially to the enzymes. This is consistent with the relatively low resolution of the densities, and similar results have been confirmed in the case of ADH and AlDH from G. oxydans . Furthermore, we confirmed a clear cavity around the FAD catalytic site in the top view of the structure (Figure C).…”
Section: Resultssupporting
confidence: 90%
“…This is consistent with the relatively low resolution of the densities, and similar results have been confirmed in the case of ADH and AlDH from G. oxydans. 63 Furthermore, we confirmed a clear cavity around the FAD catalytic site in the top view of the structure (Figure 1C).…”
Section: ■ Introductionsupporting
confidence: 55%
“…Later, Adachi et al demonstrated that by immobilizing the enzymes on MWCNTs functionalized with 1-pyrene carboxylic acid, ADH/ALDH bienzymatic bioanode can be produced. Recently, high electricity was generated by an ethanol/air BFC using this bioanode, which showed a maximum current density of 2.69 ± 0.09 mA cm −2 and a maximum power output of 0.48 ± 0.01 mW cm −2 at 0.366 ± 0.004 V [28], as shown in Figure 1d. Chansaenpak et al fabricated a BFC using a graphite electrode, which was modified with MWCNTs, as the cathode [35].…”
Section: Carbon Nanomaterialsmentioning
confidence: 89%
“…Similarly, the hydrogenase and reductase-loaded MWCNT for H 2 -driven NADH production is illustrated [27] (c), and the role of MWNCT in constructing a biofuel is depicted (d) (reprinted with permission from Ref. [28], Copyright 2023, ACS).…”
Section: Porous Carbonmentioning
confidence: 99%